The Effect of Fuel Injection on the Combustion Characteristics of Gas-Solid Two-Phase Gas - Zhao Libei, Ma Likun, Xia Zhixun, Feng Yunchao, Chen Binbin, Liu Yandong (Hangkong bingqi)
Fuel injection significantly affects the combustion characteristics of gas-solid two-phase gas in solid rocket scramjet. The effects of fuel equivalent ratio and fuel injection port arrangement on the combustion characteristics of gas-solid two-phase gas are investigated by numerical simulation in this paper. The results show that the minimum Mach number in the combustor decreases with the increase of fuel equivalent ratio under the condition of constant fuel injection mode. Compared with the increase of equivalent ratio, the improvement of fuel injection mode has a greater effect on combustion performance and mode conversion. The combustion zone of condensed phase particles in gas-solid two-phase rich combustion gas is consistent with the large temperature rise region of the combustor, and the combustion efficiency of condensed phase particles is the key factor to improve the total combustion efficiency.